Optimum Design of Coal Mine V belt Drive based on Matlab and the Simulation Analysis based on Recurdyn - Yuan Kang; Fu Qunfeng; Huang Guoxiang (Jixie chuandong)
Taking the V belt of transmission device in the coal mine belt conveyor as optimization design object and combining with both optimized design ideas and Matlab,regarding minimal gross weight of V belt pulley as optimization goals,the modeling and optimization of multi row V belt drive is carried out by using exterior penalty method,the parameter is solved out and determined with branch and bound method. Then,the multi row V belt drive kinematics simulation and dynamics simulation are carried out. The results show that,the optimum design not only make the system has compact transmission structure,lightest quality,but also has well motion characteristic and dynamics characteristic,and transfer movement well. The rationality of optimization design is verified,the reference and basis for the optimization design of the belt of transmission device in coal mine belt conveyor are provided.